Perceptions and Understandings of Low Literacy Among Developing Teacher Candidates - Baugher, Johannah; Singleton, Everett (Educational (Re)naissance, 2021)
While little is known of the perceptions held by members of the general public toward persons of low literacy background, this research study worked to inform a subset of those perceptions as held by developing teacher candidates. Additionally, this study sought to more concretely frame contributing and non-contributing factors which this same population believed influenced occurrences of low literacy. Anchored in the concept of intersectionality (Crenshaw, 1989), this study collected and analyzed 56 survey responses which yielded informative themes that further defined low literacy as an obstacle, outcome, level of performance, or degree of achievement. Teacher candidates further demonstrated an understanding that conditions of low literacy were often situationally-defined as those persons were commonly disadvantaged in some way. Candidates’ responses further purported their action plan in confronting low literacy in their classroom was founded upon these verbs: act, invest, connect, and equalize. Though this study alone is not comprehensive or absolute in its findings, it does help to inform a step of the journey that will lead to a more accurate understanding of the perceptions held of low literacy and its many, influential tentacles.